Complete androgen insensitivity syndrome or testicular feminization: review of literature based on a case report - Souhail, Regragui (Pan Afr Med J, 2016)
Testicular feminization, or the androgen insensitivity syndrome, is a rare disease. Because of various abnormalities of the X chromosome, a male, genetically XY, has some physical characteristics of a woman or a full female phenotype. Indeed the androgen insensitivity syndrome occurs because of a resistance to the actions of the androgen hormones, which in turn switches the development towards the aspect of a woman. We report a case of complete androgen insensitivity syndrome in a 30 years old woman who presented primary amenorrhea. We aim to improve our knowledge of this illness from the data that provides us this study, and a review of the literature.